(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study aimed to identify the degree of proactive leadership practice among school principals in private secondary Jordanian schools, and to determine whether there are statistically significant differences between the average responses of the study sample members according to the variables (gender, educational qualification, and practical experience). To achieve the objectives of the study, a descriptive, correlational approach was adopted, and the sample was selected using the available method, as it reached (354) individuals, representing (10.8%), of the study population. The researchers used a questionnaire consisting of two parts: the first part represents the personal variables of the study sample members, and the second part is to measure the degree of proactive leadership practice among private secondary school principals and consists of (31) items distributed over three areas. secondary Jordanian school principals as a whole and in all fields was moderate, and that there were no statistically significant differences between the responses of sample members to the degree of practicing proactive leadership among school principals according to the variables (gender, academic qualification, and practical experience).